SYURA DAN DEMOKRASI BARAT: KRITIK DAN SOLUSI MENUJU DEMOKRASI ISLAM - Toha Andiko (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Western scholars require democracy to meet the elements of tolerance, consultation, elections, balance, evaluation, separation of powers and political participation. However, in practice democracy is often equated with the experience and political traditions of Western Europe and the United States. Western countries often adopt a double standard in the conduct of democracy, this is evident from their democratic attitudes while in the country, and not democratic outside of the country. Another example of the multiparty and parliamentary electoral systems that prevail in Britain and France is not universally accepted as a single model of democracy. The Islamic democracy sometimes identified with shura is not an end in itself, but a way to arrive at the noblest goal of applying the Islamic Shari’ah. The Islamic government is a mixture of presidential and parliamentary systems. It has four organs: the presidential institution, the ahl al-Hall wa al-’Aqd council, the shura council, and the judiciary. The first three institutions are the selected institutions, therefore are directly accountable to the people. Members of judicial institutions are appointed by the President, but the President has no constitutional right to intervene in their work. The judiciary is immune from any influence, unless its decision is against the Shari’a. Thus, shura is the backbone of the Islamic political system, as the process by which it is produced and generated decisions on binding public affairs.